2023
DOI: 10.21203/rs.3.rs-2380259/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microstructural asymmetries of the planum temporale predict functional lateralization of auditory-language processing

Abstract: Structural hemispheric asymmetry has long been assumed to guide functional asymmetry of the human brain, but empirical evidence for this compelling hypothesis remains scarce. Recently, it has been suggested that microstructural asymmetries may be more relevant to functional asymmetries than macrostructural asymmetries. To investigate the link between microstructure and function, we analyzed multimodal MRI data in 907 participants. We quantified structural and functional asymmetries of the planum temporale (PT)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…The exploratory analyses of the present study did not show a relationship of PT thickness asymmetry with behavioural RTP ability as measured by GDT, nor language lateralisation as measured by the DLT. This aligns with Qin et al [27] who found a significant positive relationship of PT surface area, but not thickness with lateralisation of PT activity (measured via fMRI) in a speech comprehension task. Leftward thickness asymmetry has been linked with processing of longer-temporal window cues [i.e., rightward biased under the AST; 69].…”
Section: Planum Temporalesupporting
confidence: 90%
See 3 more Smart Citations
“…The exploratory analyses of the present study did not show a relationship of PT thickness asymmetry with behavioural RTP ability as measured by GDT, nor language lateralisation as measured by the DLT. This aligns with Qin et al [27] who found a significant positive relationship of PT surface area, but not thickness with lateralisation of PT activity (measured via fMRI) in a speech comprehension task. Leftward thickness asymmetry has been linked with processing of longer-temporal window cues [i.e., rightward biased under the AST; 69].…”
Section: Planum Temporalesupporting
confidence: 90%
“…Use of developing automatic surface-based sub-segmentation software [e.g., 172] may allow more specific analyses of the asymmetry of these PT sub-regions and their involvement in speech-related lateralisation. Furthermore, as emphasised by Qin and colleagues [27] microstructural asymmetries of the PT (intracortical myelin, content, neurite density, & neurite orientation dispersion) also show relationships with functional lateralisation for speech-processing. Although these authors claim microstructure factors to be superior variables of interest, their results also showed micro/macro to be differentially sensitive to morphological variances – a finding that we suggest is strongly meriting of conjunctive use and exploration of both microstructure and macrostructure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations